Deskripsi Konsep Diri Mahasiswa Pendidikan Teknik Otomotif Terhadap Profesi Guru : Description of the self-Concept of Automotive Engineering Education Students Toward the Teaching Profession - Andhika Rafli Syafikri; Fardhan Azhar; Wahid Munawar (Universitas Pendidikan Ganesha, 2026)
This study aims to describe the self-concept of student in the Automotive Engineering Education program at Universitas Pendidikan Indonesia toward the teaching profession. The method used is a descriptive quantitative approach involving 32 respondents selected through convenience sampling. Data were collected using a Likert-scale questionnaire. The result indicate that the aspect of students’ perceptions of the teaching profession achieved the highest percentage at 78.58% (good category), followed by perceived teaching ability at 64.26% and self-confidence at 63.61%, while interest in the teaching profession showed the lowest percentage at 51.74% (fair category). Overall, the students’ self-concept toward the teaching profession has not yet been fully and comprehensively developed